PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF TERHADAP HASIL BELAJAR MATEMATIKA KELAS XI MIA SMA N 13 PADANG - BETA INDO PUTRA (Departemen Matematika, 2018)
The problem in learning mathematics is the learning outcomes of students are not optimal. Low learning outcomes occur in class XI MIA SMA N 13 Padang. One of the causes is students are less active, so that the creativity of students has not been seen in mathematics learning. Creative-Productive learning is one of the learning strategies that can enhance the students activities and learning outcomes . The purpose of this research is to see activities and learning outcomes of students during the application of Creative-Productive Learning Strategies in mathematics lessons. This type of research is quasy-experiment with Randomized Control Group Only Design. The results of this research indicate that the activities of students tend to increase after applying Creative-Productive learning strategies. Based on the analysis of the final test results obtained learning outcomes with the application of Creative-Productive learning strategies better than the learning outcomes of students with conventional learning. It can be concluded that there is an influence the application of Creative-Productive learning strategies to the mathematics learning outcomes.Keywords— Creative-Productive learning, Mathematics Learning, students activities, learning outcomes